2021
DOI: 10.1021/acs.jafc.1c03159
|View full text |Cite
|
Sign up to set email alerts
|

Sesamol Epigenetically Induces Estrogen Receptor α Re-expression by Upregulating miR-370-3p in Estrogen Receptor α-Negative Breast Cancer

Abstract: Due to lack of estrogen receptor α (ERα, gene name: ESR1), ERα-negative breast carcinoma is insensitive to endocrine therapy, and restoration of ERα has become a promising strategy for ERα-negative breast cancer treatment. Sesamol, a naturally occurring phenolic compound, is usually extracted from sesame seeds. Previous investigations have unmasked its antioxidant and anti-inflammation properties. In this study, sesamol induced ERα functional re-expression followed by upregulation of its downstream pS2 and GRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The EE % values of sesamol in both SLNs and PNs were in the range from 40.07 ± 0.76 to 66.09 ± 0.92. These results were satisfying with respect to a small hydrophilic cargo like sesamol that can easily leak out to the surrounding aqueous environment during preparation . Additionally, there was a significant increase ( p < 0.05) regarding the loaded amount of sesamol/100 mg of carrier in the case of PNs (from 43.51 ± 0.83 μmol to 67.04 ± 0.5 μmol) over SLNs (from 6.71 ± 0.09 μmol to 9.58 ± 0.1 μmol).…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…The EE % values of sesamol in both SLNs and PNs were in the range from 40.07 ± 0.76 to 66.09 ± 0.92. These results were satisfying with respect to a small hydrophilic cargo like sesamol that can easily leak out to the surrounding aqueous environment during preparation . Additionally, there was a significant increase ( p < 0.05) regarding the loaded amount of sesamol/100 mg of carrier in the case of PNs (from 43.51 ± 0.83 μmol to 67.04 ± 0.5 μmol) over SLNs (from 6.71 ± 0.09 μmol to 9.58 ± 0.1 μmol).…”
Section: Resultsmentioning
confidence: 55%
“…It is clear that both of the loaded nanoparticles achieved a higher cytotoxic effect than pure sesamol, indicating the efficient uptake of nanoparticles by malignant cells causing better intracellular internalization of sesamol and subsequent potentiation of its effect. 4 The differences from pure sesamol were statistically significant at p < 0.05. Additionally, a carrier-mediated cytotoxic effect was noticed in the case of GMS-SLNs, inferred from the low IC 50 score of plain GMS-SLNs (179.67 ± 16.06 μM).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, sesamol has been documented to found that sesame phytoestrogen lignanscan stimulate testosterone aromatization to estradiol, or convert it to Dihydrotestosterone. High level intake of liquorice root extract or sesame oil caused hormonal disturbance and decreases sperm count [61].…”
Section: Combination Therapy Of Sesamol With Other Drugsmentioning
confidence: 99%